SIMULASI PROSES PRODUKSI KUE ALI (LEDRAM) PAK BEBEN DI DESA LEMAH DUHUR, TEMPURAN, KABUPATEN KARAWANG - Amelia Nur Fariza; Annisa Indah Pratiwi; Hendri (Industry Xplore, 2021)
Ali's cake (ledram) is one of Karawang's specialty foods which is shaped like a donut made from a mixture of rice flour, coconut milk, and brown sugar. The steps for making Ali cake (ledram) start from preparing the ingredients, cooking coconut milk, brown sugar, and granulated sugar. Next is the process of mixing rice flour into the coconut milk and sugar mixture, then proceed with the cake molding process and the frying process. The last stage of making Ali cake (ledram) is the packaging and shipping process. From the results of observations in the field, then an analysis was carried out for making conceptual models and simulations. The simulation of the Ali cake production process (ledram) was carried out using ProModel software. The simulation results show a high rate of cake delivery failure. Next, a repair scenario is made for the system that is already running, namely by adding man power. The simulation results of the improvement system show that there is no delivery failure in the cake delivery process flow. The transfer process of ready-to-pack cakes to ready-to-deliver cakes is smooth, there is no buildup or over capacity.